The Economic and Spatial Peripherality of Border Regions in Southeastern Europe - Gülden Erkut; Ceren Özgen (European Regional Science Association (ERSA), 2003)
It is obvious that trans-border co-operations are one of the most important aspects of the economic integration of European Union. In the ongoing integration process many scientific work is done with regard to borders of the countries. These scientific works propose the idea of enhancing cross-border co-operation, and the developing new economic regions while creating new opportunities for growth and employment on both sides of the borders. In this respect border-regions are considered to play a catalytic role within the ESDP. The aim of the present paper is to address a number of issues related to Turkey's status within the EU integration process and the impacts of it on the socio-economic improvement of the border regions of Turkey. One of these issues is concerned with the strategic importance of Turkey in the Eurasian context as a transit route, and the economic, institutional restructuring of Turkey within the enlargement process of EU. The other issue is to do with the transformation of border regions, how their spatial organization and economic development/restructuring are influenced by the flow of goods, people, and vehicles and by the state policies from past to present. In addition, we observe how the disparities among the eastern and the western regions of Turkey are differentiated in this process. Moreover, trans-border co-operations, that have key role within the European Spatial Development Perspective, are concerned/examined in order to formulate the relations among Balkan regions and western border regions of Turkey, that are the primary linkages and which strive to integrate into EU.
Keywords: 330